Variables influencing truth reconciliation commissions to promote post-conflict peacebuilding and statebuilding in Africa: a South African experience - Niyitunga, Eric B. (Frontiers in Political Science, 2024)
Truth and reconciliation commissions (TRCs) are understood to offer cheap justice, a justice not bound by the law. South African experience in the post-apartheid era shows that they are significant tools for peacebuilding as well as statebuilding. The experience shows that the use of TRCs has created an authoritative record of what happened; enabled the victims to tell their stories without fear or embarrassment, and recommended legislative, structural and institutional reforms that avoided the repetition of past abuses. Successful peace and statebuilding are based on the above in order to achieve sustainable peace. TRCs promote rule of law, human rights protection, and ensure healing and freedom for all. However, the relapses of conflicts and political tensions, intercommunal hatred and divisions in African countries, create more questions than answers. These continuous issues show that TRCs have instead not resolved conflicts. The paper found that TRCs can only lead to successful peacebuilding and statebuilding if there is willingness on the side of the citizens as well as their political leaders. There is need to learn from the South African experience to ensure that TRCs lead to successful peacebuilding and statebuilding. The paper relied on historical research designed to study TRCs in Africa.